Effect of electrical spot welding on load deflection rate of orthodontic wires - Alavi, Shiva (Dent Res J (Isfahan), 2015)
BACKGROUND: One of the methods used for joining metals together is welding, which can be carried out using different techniques such as electric spot welding. This study evaluated the effect of electric spot welding on the load deflection rate of stainless steel and chromium-cobalt orthodontic wires. MATERIALS AND METHODS: In this experimental-laboratory study, load deflection rate of 0.016 × 0.022 inch stainless steel and chromium cobalt wires were evaluated in five groups (n =18): group one: Stainless steel wires, group two: chromium-cobalt wires, group three: stainless steel wires welded to stainless steel wires, group four: Stainless steel wires welded to chromium-cobalt wires, group five: chromium-cobalt wire welded to chromium-cobalt wires. Afterward, the forces induced by the samples in 0.5 mm, 1 mm, 1.5 mm deflection were measured using a universal testing machine. Then mean force measured for each group was compared with other groups. The data were analyzed using repeated measure analysis of variance (ANOVA), one-way ANOVA, and paired t-test by the SPSS software. The significance level was set as 0.05. RESULTS: The Tukey test showed that there were significant differences between the load deflection rates of welded groups compared to control ones (P < 0.001). CONCLUSION: Considering the limitation of this study, the electric spot welding process performed on stainless steel and chromium-cobalt wires increased their load deflection rates.